Bee Pollen: Current Status and Therapeutic Potential - Khalifa, Shaden A M; Elashal, Mohamed H; Yosri, Nermeen; Du, Ming; Musharraf, Syed G; Nahar, Lutfun; Sarker, Satyajit D; Guo, Zhiming; Cao, Wei; Zou, Xiaobo; Abd El-Wahed, Aida A; Xiao, Jianbo; et al. (Nutrients, 2021)
Bee pollen is a combination of plant pollen and honeybee secretions and nectar. The Bible and ancient Egyptian texts are documented proof of its use in public health. It is considered a gold mine of nutrition due to its active components that have significant health and medicinal properties. Bee pollen contains bioactive compounds including proteins, amino acids, lipids, carbohydrates, minerals, vitamins, and polyphenols. The vital components of bee pollen enhance different bodily functions and offer protection against many diseases. It is generally marketed as a functional food with affordable and inexpensive prices with promising future industrial potentials. This review highlights the dietary properties of bee pollen and its influence on human health, and its applications in the food industry.
Keywords: nutritional value; metabolic syndromes; nutriční hodnota; Humans; Carbohydrates; sacharidy; human health; krysa rodu Rattus; lidé; Antioxidants; Blood Glucose; Functional Food; zvířata; myši; včely; functional food; Mice; metabolický syndrom; antioxidancia; Nutritive Value; Bees; propolis; Pollen; krevní glukóza; Metabolic Syndrome; Propolis; Rats; bee pollen; pyl; Animals; funkční potraviny